Leptin receptor signaling mediates the distinct tendon–bone interface reconstruction in rotator cuff tears and osteoporosis-comorbid rotator cuff tears - Zhu, Dongxu; Zhu, Xinrui; Zhang, Yingze; Huang, Xiaohong (Stem cell research & therapy, 2025)
Background The intact tendon-bone interface (TBI) consists of four histological layers--tendon, fibrocartilage, calcified fibrocartilage, and bone--that gradually merge into each other, making complete structural restoration after injury challenging. Osteoporosis poses a significant risk for rotator cuff tears (RCTs) and re-tears after arthroscopic rotator cuff repair (ARCR). Activating Leptin receptor (Lepr) mediated Stat3 signaling transduction facilitates the transcription of Runx2 and Sox9, respectively, and promotes osteogenesis and chondrogenesis. Materials and methods Sixty-five female Sprague Dawley rats were used. Animal models--ovariectomy (OVX) and rotator cuff tear and repair (RC)--were employed to simulate typical tendon-bone healing and TBI reconstruction under deficient bone-forming capability. And, grip strength, transcriptome, ELISA, histochemistry, and qPCR were performed to reveal the distinct functional recovery between RC and OVX + RC rats, as well as pathophysiologic exhibition in the TBI at 2-week and 8-week. Results RC rats exhibited better functional recovery during the proliferative phase of TBI reconstruction, i.e., 2-week, compared to OVX + RC rats, while both RC and OVX + RC rats showed a lower grip strength in the upper limbs during the remodeling phase, i.e., 8-week. In RCTs, where adipogenesis was suppressed in RCT healing, the osteoblast-derived Leptin (Lep) and Angiopoietin like 4 (Angptl4), the Lepr ligands, facilitate osteogenesis and chondrogenesis, resulting in an obvious mineralized band in the reconstructed TBI and a transit cartilage band during the proliferative phase in RC rats. In osteoporosis-comorbid RCTs, where osteogenesis was suppressed while adipogenesis was activated, the adipocyte-derived Lep and Angptl4, particularly Angptl4, facilitated Stat3 phosphorylation and nucleus transfer, Sox9 transcription, and chondrogenesis, which was observed in OVX + RC rats and led to excessive cartilage regeneration. Conclusions This study demonstrated the role of Lep and Angptl4 in TBI reconstruction, via activating Lepr-mediated Stat3-Sox9 and Stat3-Runx2 signaling pathways, differentially regulating osteogenesis and chondrogenesis, and leading to the distinct clinical outcomes post-ARCR in RCTs and osteoporosis-comorbid RCTs. This study provides fundamental support for increasing Angptl4 in situ for chronogenesis in RCTs and lowering Angptl4 to Lep ratio for osteogenesis in RCTs with osteoporosis comorbidity. Keywords: Rotator cuff tears, Osteoporosis, Tendon-bone interface, Leptin receptor, Leptin, Angiopoietin like 4